2020
DOI: 10.1039/c9sc05208a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ring-strain on the ultrafast photochemistry of cyclic ketones

Abstract: Ultrafast spectroscopy of ring-opening in three cyclic ketones reveals how ring-strain affects Norrish Type-I α-cleavage mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 53 publications
(57 reference statements)
2
10
0
Order By: Relevance
“…15 Additionally, the result aligns with a recent TA study of the C-C bond cleavage of cyclopentanone in cyclohexane following 255 nm photoexcitation, which Kao et al found occurred in r1 ps. 16 Likewise the t 2 component [1.8 AE 0.2 ns] for the rate of formation of 3 [22] from 1 [22] is consistent with previously reported ISC timescales for acyl-alkyl diradicals. 17 Spectral evolution by ns-TA spectroscopy was also monitored (Fig.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…15 Additionally, the result aligns with a recent TA study of the C-C bond cleavage of cyclopentanone in cyclohexane following 255 nm photoexcitation, which Kao et al found occurred in r1 ps. 16 Likewise the t 2 component [1.8 AE 0.2 ns] for the rate of formation of 3 [22] from 1 [22] is consistent with previously reported ISC timescales for acyl-alkyl diradicals. 17 Spectral evolution by ns-TA spectroscopy was also monitored (Fig.…”
supporting
confidence: 87%
“…10,11 Furthermore, reaction with hydrazines gave high yielding access to phthalazones (e.g. 16,17,21), which are important pharmacophores present in the chemotherapeutic agent olaparib (Lynparza s ), 12 and azelastine (Astelin, Optivar, Allergodil), a frontline drug treatment for mild rhinitis. 13 By contrast, o-phenylenediamine, ethanolamine and ethylenediamine gave lactols 18 -20 respectively.…”
mentioning
confidence: 99%
“…TEAS measurements on timescales from 100 fs to 1.3 ns used an apparatus at the University of Bristol which has been described elsewhere. 44,45 TVAS experiments used a custom-built laser system in the LIFEtime facility at the Rutherford Appleton Laboratory 46 to make transient IR spectroscopy measurements over time delays from 300 fs to 10 ms which provided specic information on the chemical participants in sequential reaction steps. In both types of spectroscopic studies, samples were continuously circulated through a Harrick cell using a sealed ow system.…”
Section: Resultsmentioning
confidence: 99%
“…8,9,13,14,24 To examine how metal-ion coordination affects the photochemical dynamics, we compare the internal conversion and intersystem crossing rates of ACP in solutions without and with dissolved Mg 2+ or Li + salts using ultrafast transient electronic absorption spectroscopy (TEAS). Detailed descriptions of the ultrafast laser system have been published elsewhere, 25,26 and the Supporting Information provides a summary as well as further experimental details.…”
mentioning
confidence: 99%